Особливості адресатної семантичної залежності в структурі базових синтаксичних конструкцій - Масицька, Тетяна Євгенівна; Masуtska, Tetiana (Східноєвропейський національний університет, 2013)
У статті розглянуто адресатну семантичну залежність в структурі базових синтаксичних конструкцій. Визначено основні групи дієслівних предикатів, які формують адресатну семантичну залежність. Проаналізовано функційне вираження адресатної семантичної залежності в реченнєвих моделях. The functional features of addressee semantic dependencies in the structure of the basic syntactic sentences are resolved in this article. The main groups of verb predicates that form addressee semantic dependencies are determined. The analysis of semantic and syntactic structure of the sentence makes possible to distinguish semantic types of addiction. Semantic type of predicate forms structures of sentence, defines the types of dependencies between its components, provides an opportunity to explore different constructions. The functional position of addressee semantic dependency in the structure of sentence is analyzed. The research concluded that the addressee semantic-syntactic relations in the simple sentence directed from a subordinate (dependent) component to the subordinates (the reference), which is the verbal predicate in the most cases.
The Features of Addressee Semantic Dependence in the Structure of the Basic Syntactic Sentences
Keywords: реченнєва конструкція; дієслівний предикат; синтаксична залежність; семантична залежність; адресатна семантична залежність; construction of sentence; predicate verb; syntactic dependency; semantic relationship; addressee semantic dependency